2016
DOI: 10.1039/c5cc09164k
|View full text |Cite
|
Sign up to set email alerts
|

Dual-responsive nanoparticles release cargo upon exposure to matrix metalloproteinase and reactive oxygen species

Abstract: Micellar nanoparticles were designed to be responsive to matrix metalloproteinases (MMPs) and reactive oxygen species (ROS), each of which is upregulated in the pathology of inflammatory diseases. The amphiphilic polymer-based nanoparticle system consists of a hydrophilic shell responsible for particle morphology change and aggregation, together with a hydrophobic block designed to release cargo in the presence of ROS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…It can be useful as a trigger for cargo release, similar to already demonstrated amphiphilic polymerbased nanoparticle systems with drug release enzymatic response. 54 We further demonstrated that minute alteration in the disordered peptide sequence and dendrimer architecture could significantly impact the nanoscopic and macroscopic lengthscales. This platform also enables in-situ modifications of the IDPs and the study of the mutual interaction between IDPs.…”
Section: Resultsmentioning
confidence: 79%
“…It can be useful as a trigger for cargo release, similar to already demonstrated amphiphilic polymerbased nanoparticle systems with drug release enzymatic response. 54 We further demonstrated that minute alteration in the disordered peptide sequence and dendrimer architecture could significantly impact the nanoscopic and macroscopic lengthscales. This platform also enables in-situ modifications of the IDPs and the study of the mutual interaction between IDPs.…”
Section: Resultsmentioning
confidence: 79%
“…Boronate ester–based ROS sensitivity was also exploited by Daniel et al., where they designed a block copolymer prodrug system that could self‐assemble in aqueous conditions to form particles. The prodrug consisted of an inhibitor for MMPs, which are commonly found in areas of increased ROS concentration, tethered to the polymer backbone through an aryl boronic ester moiety.…”
Section: Methods Of Stimuli‐responsive Drug Deliverymentioning
confidence: 99%
“…Other systems are responsive to a combination of different stimuli. The association of MMP- and reactive oxygen species (ROS)-responsiveness enabled Daniel et al [ 215 ] to use amphiphilic polymer NPs in inflammatory diseases, such as myocardial infarction, arthritis, ischemia and atherosclerosis, where both are upregulated. With this design approach they achieved specific in vivo targeting of ischemic skeletal muscle [ 216 ], avoiding off-target accumulation in healthy muscle and regulating macrophage internalization [ 217 ].…”
Section: Stimuli Responsivenessmentioning
confidence: 99%